Diversity of Morphological Characteristics of Kaliandra Flowers (Calliandra spp.) in the Highland Forest of Mount Ciremai National Park, Indonesia - Sukron Aminudin; Zaenal Abidin (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Knowledge of the morphological characteristics of kaliandra flowers (Calliandra spp.) that live naturally in highland forests in conservation areas can provide an understanding related to their adaptation to the growing environment and support efforts to preserve endemic plants. This study aims to see the diversity of morphological characteristics of red kaliandra (Calliandra calothyrsus) and white kaliandra (Calliandra portoricensis) flowers in Mount Ciremai National Park. Plant selection was carried out using the purposive sampling method with the following criteria: 1). the position of the plant can be reached, 2). It has good flower morphological conditions, is not deformed, and is dry. Observations were made at 14.00 local time to get good flower conditions, and documented. Then the morphological data was analyzed using the descriptive and visualized qualitative method. The results of the study showed that almost all morphological variables had similarities, but there were different variables in these two types, namely the color of the stamens, the color of the petals and the flower crown.